If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 86 = 8x + -9 Reorder the terms: 86 + 3x = 8x + -9 Reorder the terms: 86 + 3x = -9 + 8x Solving 86 + 3x = -9 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 86 + 3x + -8x = -9 + 8x + -8x Combine like terms: 3x + -8x = -5x 86 + -5x = -9 + 8x + -8x Combine like terms: 8x + -8x = 0 86 + -5x = -9 + 0 86 + -5x = -9 Add '-86' to each side of the equation. 86 + -86 + -5x = -9 + -86 Combine like terms: 86 + -86 = 0 0 + -5x = -9 + -86 -5x = -9 + -86 Combine like terms: -9 + -86 = -95 -5x = -95 Divide each side by '-5'. x = 19 Simplifying x = 19
| 14+6a-8=28 | | -4x^2+10x+6=0 | | (x+7)(x-7)=32 | | 8x-11=-3x-4 | | 5(X-1)=10-2(3X+2) | | 3x^2-12x(1.5)= | | 5+.5c=14 | | 2(x-5)-x=-6 | | 72-5x=13x+20 | | 6+5n=9-2n | | 0.07x*0.03=0.38 | | 1.4(a+6)=2.8(a+10) | | -97-8x=60-22x | | 112=1.5s | | 6x(2x+7)= | | 9+3(-7y+1)=6(y+7)+6 | | 50+65+x=505 | | 4x-3=7x+18 | | 6x(2x-7)= | | 9x=14x-21 | | -7x+11=19-x | | 3+10n=12n-3 | | 0-5x=6x+19 | | (y/4)=-10 | | g(x)=x^2-2X+5 | | x^3+3sinx+2cosx=2 | | 85-6x=w | | 2-5y=18 | | 3x-7+4=28 | | 2432+42= | | 5x+2+4x=7+2x-4 | | 2432+4= |